(untitled) (Journal of Universal Science Research, 2023)
The article is devoted to the analysis of the names of diseases used in the process of communication between a doctor and a patient. Particular attention is paid to the criteria for the availability of special information for those who act as patients. The author conducts typological studies of the characteristic features of the names of diseases and makes an attempt to classify them, taking into account the possible stylistic range of these nominations